Ответ:=27
Объяснение:
ACxAB= IACI*IABI*cos∡A
IABI² = (Xa-Xb)²+(Ya-Yb)²+(Za-Zb)²= (-1-3)²+(-2-2)²+(1-3)² =16+16+4=36
IABI=6
=> По теoреме Пифагора
IACI²=IABI²-ICBI²=36-9=27
iACI=3√3
cos∡A=AC/AB=3√3/6 =√3/2
=> IACI*IABI*cos∡A =3√3*6*√3/2 =27
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:=27
Объяснение:
ACxAB= IACI*IABI*cos∡A
IABI² = (Xa-Xb)²+(Ya-Yb)²+(Za-Zb)²= (-1-3)²+(-2-2)²+(1-3)² =16+16+4=36
IABI=6
=> По теoреме Пифагора
IACI²=IABI²-ICBI²=36-9=27
iACI=3√3
cos∡A=AC/AB=3√3/6 =√3/2
=> IACI*IABI*cos∡A =3√3*6*√3/2 =27